Inclusive Education for Children with Special Needs : Some Reflections from Odisha, India - Das, Ansuman; paltaSingh, tattWaMaSi (JOURNAL OF INDIAN EDUCATION, 2024)
Inclusive education is based on the notion that every child should share the same classroom, regardless of caste, ethnicity, age, gender or disability. It recognises every learner’s potential, and each child’s specific needs and abilities. There are several obstructing factors, such as inappropriate curriculum, lack of trained teachers, insufficient financial provisions, unfitting infrastructure and classroom environment, that affect the teaching learning process. Using empirical data, the study was conducted in one of the blocks of western Odisha and has emphasised the need for inclusive school environment, better support mechanism and societal awareness. The study examines the challenges confronted by CwSNs in pursuing their education, and assesses parental and teachers’ awareness. It was revealed that most of the schools did not have CwSN friendly TLMs and IED trained teachers. The need for better infrastructure and specialised care for the CwSNs in an inclusive environment was felt by all the participants.